Does the implementation of pay-for-performance indicators improve the quality of healthcare? First results in France - Sanchez, Marc-Antoine; Sanchez, Stéphane; Bouazzi, Leila; Peillard, Louise; Ohl-Hurtaud, Aline; Quantin, Catherine (Frontiers in Public Health, 2023)
Background: Pay-for-performance (P4P) models are intended to promote quality of care in both hospitals and primary care settings. They are considered as a means of changing medical practices, particularly in primary care. Objectives: The first objective of this study was to assess how performance indicators changed over time, measured through "Remuneration on Public Health Objectives" (ROSP) scores, between 2017 and 2020 in a large French region (Grand Est region), and to compare this evolution in the rural vs urban areas of the region. The second objective was to focus on the area with the least improvement in ROSP scores and to investigate whether the scores and the available sociodemographic characteristics of the area were associated. Methods: First, we measured the evolution over time of P4P indicators (i.e.ROSP scores) obtained from the regional health insurance system, for GP practices in the Grand Est region between 2017 and 2020. We then compared the scores between the Aube Department and the rest of the region (urban areas). To address the second objective, we focused on the area found to have the least improvement in indicators to investigate whether there was a relationship between ROSP score and sociodemographic characteristics. Results: More than 40,000 scores were collected. We observed an overall improvement in scores over the study period. The urban area (Grand Est region minus the Aube) scored better than the rural area (Aube) for chronic disease management (median 0.91 (0.84-0.95)vs0.90(0.79-0.94), p<0.001) and prevention (median 0.36(0.22-0.45)vs0.33(0.17-0.43), p<0.001), but not for efficiency, where the rural area (Aube) performed better (median 0.67(0.56-0.74) vs0.69(0.57-0.75 in the rest of the Grand Est region, p=0.004). In the rural area, we found no significant association between ROSP scores and sociodemographic characteristics, except for extreme rurality in some sub-areas. Conclusions: At the regional level, the overall improvement in scores observed between 2017 and 2020 suggests that the implementation of ROSP indicators have improved the quality of care, particularly in urban areas. These results also suggest that efforts should be focused on rural areas, which already had the lowest scores at the start of the P4P program.